Entrepreneurship in the Cultural Industries in Southeast Asia - Tran, Huyen Trang (2015)
The aim of this thesis is to introduce to whomever it may concern the new socio-economical phenomenon Korea has brought to the global creative industry. The term Hallyu will be clarified in all its details and after understanding the whole meaning behind it, the reader will be fully aware of all circumstances concerning the main topic of this thesis -- K-pop. The Korean entertainment industry is already very unique as it is on its own, but it is even more worth looking at when comparing to the global music industry in general. A thorough inside look into K-pop's globalization strategy, its venture-like approach of the creative industry as well as curiosities and confrontational issues around it will be explained in here.